Volatile systematics: A novel biochemical interpretation of essential oil compounds enhances their chemophenetic significance. (October 2020) - Evergetis, Epameinondas; Haroutounian, Serkos A.
Abstract: The Essential Oils (EOs) present numerous chemophenetic applications, mostly at infrageneric rank. EOs utilization for this purpose has been questioned because of the external stimulations that control their chemodiversity and quantitative composition. Therefore, they are considered as a class of natural products with questionable systematic significance. Present study exploiting the recent advances on plant volatile biogenesis aims to reestablish and expand the EOs chemophenetic significance. The presented methodology translates EO composition in a biochemical profile, through the chemical structure classification of EOs compounds that links their presence with the activation of endogenous biochemical procedures. The Apiaceae supra - generic classification was utilized to test the proposed methodology. In specific, 44 Greek indigenous Apiaceae taxa, representing all 10 tribes of Apioideae subfamily were collected, distilled and analyzed. The herein applied approach was focused in tribal rank and revealed 10 biochemical entities established on the diversification of their fundamental metabolic routes and biosynthetic pathways activation. The generated biochemical profiles were proven compatible with phenotypic and phylogenetic approaches, but also separated all tribes of Apioideae. Therefore, the proposed methodology can be considered as a promising new systematic tool, which is able to exploit the vast availability of EOs composition data. Highlights: Chemophenetic translation of EOs generates a biochemical profile. EOs biochemical profiles present systematic and phylogenetic significance. EOs biochemical profiles address Apioideae subfamily tribal discrepancies. EOs chemophentics applicable at suprafamily and infrageneric levels. Elucidation of endogenous plant biochemical procedures.